Parallels between spacing effects during behavioral and cellular learning - Kornmeier, Jürgen; Sosic-Vasic, Zrinka (Frontiers in Human Neuroscience, 2012)
Repeated learning improves memory. Temporally distributed (“spaced”) learning can be twice as efficient than massed learning. Importantly, learning success is a non-monotonic maximum function of the spacing interval between learning units. Further optimal spacing intervals seem to exist at different time scales from seconds to days. We briefly review the current state of knowledge about this “spacing effect” and then discuss very similar but so far little noticed spacing patterns during a form of synaptic plasticity at the cellular level, called long term potentiation (LTP). The optimization of learning is highly relevant for all of us. It may be realized easily with appropriate spacing. In our view, the generality of the spacing effect points to basic mechanisms worth for coordinated research on the different levels of complexity.